IT Workforce - Wiesche, Manuel (2021)
IS researchers have devoted significant attention to the IT workforce since the inception of MIS Quarterly (Jenkins and Johnson 1977). From 1977 to 2020, MIS Quarterly has published 85 articles that have employed diverse methods for examining the individual, organizational, and market issues tied to staffing the IT function in an organization. These studies illuminate not only how changing technologies and market conditions affect demand for the skills and competencies of IT professionals, but also how they influence the design and career paths associated with IT jobs.